Identifying drug allergies by means of exposure testing – the frequency and nature of hypersensitivity reactions - Welponer, Tobias; Brandlmaier, Matthias; Feuerstein, Bernd; Wolfgang Bauer, Johann (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Drug hypersensitivity reactions are dose-independent, unpredictable, and immune-mediated type B adverse drug reactions (ADR) in patients sensitized to a certain drug [1]. The first signs appear within minutes to hours of drug intake, ranging from low-grade to possibly life-threatening anaphylactic symptoms; they can also appear several hours to days later in the form of exanthema [2]. An allergic reaction should be substantiated within 4 weeks to 6 months after the reaction, aiming to identify the trigger and assess the risk for subsequent reactions [3]. Clinical classification, based on the morphology and timing of the reaction, is necessary for correct diagnosis. In the case of distinct symptoms of hypersensitivity and unambiguous findings of validated skin (in vivo) and/or laboratory tests (in vitro), the assignment to a trigger may be considered sufficient [4]. However, skin and laboratory tests lack high sensitivity and frequently show false negative or non-significant results [5].